2021
DOI: 10.1016/j.csbj.2021.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential descriptors of water-soluble fullerene derivatives responsible for antitumor effects on lung cancer cells via QSAR analysis

Abstract: Graphical abstract A series of water-soluble fullerene derivatives are synthesized to produce antitumor effects on three types of lung cancer cells. The fullerene compounds with sulfur-containing aromatic rings showed the most effective inhibition on cell proliferation among all fullerene compounds. The quantitative structure–activity relationship (QSAR) models illustrate that thiophene moiety in the fullerene cage has positive correlation with the antitumor effect of the fullerene derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…This has the potential to further summarize physiochemical and biological analyses to predict toxicity effects or establish ideal nanomaterials. Several QSAR modeling studies have been conducted to better comprehend the nanotoxicity of chemical substitutes such as NPs, metal oxides, and fullerenes [ 97 , 98 , 99 ]. To avoid animal testing, some governments use QSAR tools for toxic hazard prediction.…”
Section: Emerging Methods To Evaluate Toxicity Of Nanoparticlesmentioning
confidence: 99%
“…This has the potential to further summarize physiochemical and biological analyses to predict toxicity effects or establish ideal nanomaterials. Several QSAR modeling studies have been conducted to better comprehend the nanotoxicity of chemical substitutes such as NPs, metal oxides, and fullerenes [ 97 , 98 , 99 ]. To avoid animal testing, some governments use QSAR tools for toxic hazard prediction.…”
Section: Emerging Methods To Evaluate Toxicity Of Nanoparticlesmentioning
confidence: 99%
“…Reaction of chlorofullerene C 60 Cl 6 with methyl 2-(thiophen-2-yl)acetate, followed by the treatment with PPh 3 /H 2 O and hydrolysis of the ester groups, allowed us to obtain compound 5 , as described in our recent work [ 18 ]. Synthesis and characterization of fullerene derivatives 1 [ 16 ], 2 [ 19 ], 4 [ 19 ], and 5 [ 18 ] was reported earlier. Compound 3 was obtained as described in the Supplementary Materials and characterized in the form of a tert -butyl ester ( 3 -OtBu).…”
Section: Methodsmentioning
confidence: 99%
“…The unique physicochemical properties of fullerenes, as well as their ability to penetrate the cell membrane [15,16], suggest their applicability in biomedicine, in particular, as vectors for drug delivery [14,17]. A number of studies have demonstrated that fullerenes and their derivatives have antitumor activity [18][19][20]. In addition, the use of fullerenes in photodynamic therapy [21][22][23] and as carriers of radioactive atoms for the treatment or diagnosis of oncological diseases [24][25][26] seems very interesting.…”
Section: Introductionmentioning
confidence: 99%